Factors affecting the willingness of patients with type 2 diabetes to use digital disease management applications: a cross-sectional study - Mingjiao Zhang; Mingjiao Zhang; Hao Zhang; Rong Zhu; Huiqi Yang; Mengjie Chen; Xiaoxia Wang; Zhe Li; Zhe Li; Zhenzhen Xiong (Frontiers Media S.A., 2023)
BackgroundThe global burden of type 2 diabetes has significantly increased, leading to a considerable impact on healthcare systems worldwide. While the advent of mobile healthcare has provided some relief by addressing the shortage of certain medical resources, its adoption among the Chinese population remains relatively low. To extend the benefits of mHealth to a greater number of Chinese diabetic patients, it is essential to investigate the factors that influence their willingness to utilize it and implement targeted interventions based on these influencing factors. The Technology Acceptance Model (TAM) is widely employed to examine users' ultimate usage behaviors, and previous studies have indicated the potential relevance of the Perceived Risk (PR) theory and the eHealth Literacy Theory to users' usage behaviors.ObjectiveOur objective was to investigate the determinants that affect the willingness of Chinese patients diagnosed with type 2 diabetes patients to utilize digital disease management applications (DDMAs).MethodsWe conducted a cross-sectional study of patients with type 2 diabetes in three tertiary general hospitals in Chengdu using questionnaires designed by the investigators. Participants were sampled using a convenience sampling method. The questionnaire comprised three sections: socio-demographic profile and medical history; current awareness and willingness to use digital disease management applications; and the current level of e-health literacy. Structural equation modeling was employed to assess the impact of patient awareness of DDMAs and e-health literacy on the willingness to use such DDMAs.Results(1) Patients' attitudes toward using DDMAs were significantly influenced by perceived ease of use (β = 0.380, P < 0.001) and perceived usefulness (β = 0.546, P < 0.001); (2) Electronic health literacy exerted a significant impact on patients' perceived usefulness (β = 0.115, P = 0.018) and perceived ease of use (β = 0.659, P < 0.001); (3) Patients' willingness to use was significantly influenced by perceived usefulness (β = 0.137, P < 0.001) and use attitude (β = 0.825, P < 0.001).ConclusionsThe present research findings hold both theoretical and practical significance, and can serve as a guide for healthcare practitioners and researchers to gain a deeper comprehension of the acceptance of digital disease management applications (DDMAs) among type 2 diabetes patients.